BUDDING INDO-MYANMAR RELATIONS: RISING BUT LIMITED CHALLENGES FOR CHINA. Issue 4 (8th August 2019) - Peng, Nian
Abstract : There is a big gap on the study of Indo-Myanmar relations between India and China, in which the Indian experts are mainly concerned about the serious consequences of the China factor, while few Chinese scholars focus on Indo-Myanmar relations. This article, therefore, looks into the post-Cold War Indo-Myanmar relations from a Chinese perspective, so as to fill the research gap. It argues that India's influence upon Sino-Myanmar relations is actually marginal, though it has established a budding relationship with Myanmar through deepening political engagement, naval cooperation and physical connectivity with the country. The main reason is that India lacks full capability to develop the bilateral relations with Myanmar and thus compete fully with China. Additionally, the suspicion and resistance from the Burmese elite and local communities constitutes another major obstacle to the further engagement between India and Myanmar. Naypyidaw, notwithstanding its efforts to advance Indo-Myanmar relations, would prefer to gain benefits from both China and India.